Ship-course modeling and control using the SIMSCAPE physical modeling environment. (April 2021) - Fernandez de Canete, Javier; Martin-Aguilar, Jesus
Simulation is an important tool for evaluating the design of a ship-course control system. The object-oriented modeling supports the physical modeling of a multi-domain dynamical system by using a hierarchical acausal structure, as compared to block diagrams or differential equation-based causal structures. In this paper we describe the use of the SIMSCAPE simulation environment for the physical modeling-based design of the course control system of a ship. The complete model has been implemented by using this physical modeling approach whereby dynamic system equations are transformed into a diagram of interconnected physical blocks so as to represent in this way the true structure of the modeled system. The performance of the course control of the ship model was analyzed by simulation in light of the existing hypothesis and indirect validation tests previously performed with operational data. The results obtained by using sequences of course-changing maneuvers with varying disturbances serve to demonstrate the usefulness of the physical modeling-based approach with high accuracy and small computational cost as compared to the classical differential equation-based or the adimensional block-oriented diagrams. This methodology can be easily extended to other engineering fields provided that a suitable set of SIMSCAPE physical libraries can be used (electrical, mechanical, hydraulics, thermal, …). In fact, the ship-course control system model here developed represents an interesting benchmark in the field of engineering systems to get insight on the physical modeling approach under SIMSCAPE or even under MODELICA, despite its specificity to marine systems.